IMPROVEMENT OF THE ORGANIZATION AND IMPLEMENTATION OF INTERNAL AUDIT SERVICES IN MINISTRIES AND AGENCIES (CASE OF THE MINISTRY OF CONSTRUCTION OF THE REPUBLIC OF UZBEKISTAN) - HAYITOV ODILJON MUSOQULOVICH (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. In the context of public sector modernization and fiscal discipline reforms, internal audit systems play a critical role in ensuring accountability, transparency, and performance efficiency within government institutions. The construction sector, characterized by capital-intensive projects, long-term infrastructure investments, and complex procurement mechanisms, presents elevated financial, operational, and corruption-related risks. This study aims to develop and empirically substantiate an improved model for organizing and implementing internal audit services in ministries and agencies, using the Ministry of Construction of the Republic of Uzbekistan as a case study. The research integrates institutional analysis, risk-based auditing methodology, comparative international benchmarking, and performance indicator modeling. A mixed-method research design was applied, including document analysis, expert interviews (n=28), audit case evaluation (2019–2024), and quantitative modeling of internal control effectiveness indicators. Statistical analysis (correlation coefficients, regression modeling, risk-weighted performance index) demonstrates that the integration of risk-based planning, digital audit platforms, and KPI-driven evaluation increases audit efficiency by 27–34% compared to traditional compliance-based approaches. The scientific novelty of the research lies in proposing a digital-integrated risk- based internal audit framework tailored to the construction sector, incorporating predictive analytics, performance scoring matrices, and automated compliance tracking. The findings confirm that strengthening institutional independence, introducing real-time monitoring systems, and implementing performance-based audit evaluation significantly reduce financial losses, improve project delivery timelines, and enhance governance transparency.